EFFECT OF CORPORATE GOVERNANCE (WOMAN’S EXECUTIVE BOARD), COMPANY SIZE AND LEVERAGE ON PROFIT MANAGEMENT - Siska Octaviani; Ely Kartikaningdyah (Pusat P2M Politeknik Negeri Batam, 2019)
The purpose of this study was to measure the effect of corporate governance (female membership), company size and leverage on profits in companies on the Indonesia Stock Exchange (BEI) in 2012-2016. The variables used in this study are size variables, and the variable used in this study is earnings management that uses discretionary accruals using the Dechow et. Al. (1995). Withdrawal of the research sample using purposive sampling method that gets 225 samples of manufacturing companies and data which are data panels. This study conducts multiple regression with multiple regression with Eviews version 10. The results of this study indicate that the female board of directors who are insightful with earnings management when the female board of commissioners, women's audit committee, company size, and leverage do not affect earnings management.